Global strategy for the prevention and control of sexually transmitted infections : 2006-2015 : breaking the chain of transmission (WHO GenevaCH, 2007)
Deals with methods to promote healthy sexual behaviour, protective barrier methods, effective and accessible care for STIs, and the upgrading of monitoring and evaluation of STI control programmes. A section on advocacy offers advice to programme managers on approaches to mobilizing the high-level political commitment that forms the essential foundation for an acclerated response.
Keywords: SEXUALLY TRANSMITTED DISEASES